2023
DOI: 10.1002/jcp.30995
|View full text |Cite
|
Sign up to set email alerts
|

Potential roles of heparanase in cancer therapy: Current trends and future direction

Abstract: Heparanase (HPSE; heparanase‐1) is an endo‐β‐glucuronidase capable of degrading the carbohydrate moiety of heparan sulfate proteoglycans, thus modulating and facilitating the remodeling of the extracellular matrix and basement membrane. HPSE activity is strongly associated with major human pathological complications, including but not limited to tumor progress and angiogenesis. Several lines of literature have shown that overexpression of HPSE leads to enhanced tumor growth and metastatic transmission, as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 159 publications
0
0
0
1
Order By: Relevance
“…Пошук інгібіторів гепаранази як протипухлинних засобів призвів до розробки чотирьох речовин: мупар фостату (PI88), піксатимоду (PG545), ронепарстату (SST0001) і некупара нібу (M402), які пройшли клінічні випробування [62,63]. Незважаючи на вражаючі ефекти в різних доклі нічних моделях, клінічні дані вияви лися менш переконливими, а розроб лення деяких з цих сполук припине но або призупинено [62].…”
Section: основні механізми антиметастатичної дії нфг і нмгunclassified
“…Пошук інгібіторів гепаранази як протипухлинних засобів призвів до розробки чотирьох речовин: мупар фостату (PI88), піксатимоду (PG545), ронепарстату (SST0001) і некупара нібу (M402), які пройшли клінічні випробування [62,63]. Незважаючи на вражаючі ефекти в різних доклі нічних моделях, клінічні дані вияви лися менш переконливими, а розроб лення деяких з цих сполук припине но або призупинено [62].…”
Section: основні механізми антиметастатичної дії нфг і нмгunclassified
“…Recently, it has been shown that heparanse-1 is upregulated by HCV infection and favours its replication [177]. Heparanase-1 has been involved in tumour growth [178], and it may be related to hepatocarcinoma-induced HCV infection. Further studies are required in this area.…”
Section: Other Strategiesmentioning
confidence: 99%